2018
DOI: 10.3389/fnins.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Effects of Immunotherapy With Antibodies Targeting α-synuclein in a Transgenic Model of Synucleinopathy

Abstract: Synucleinopathies represent a group of neurodegenerative disorders which are characterized by intracellular accumulation of aggregated α-synuclein. α-synuclein misfolding and oligomer formation is considered a major pathogenic trigger in these disorders. Therefore, targeting α-synuclein species represents an important candidate therapeutic approach. Our aim was to analyze the biological effects of passive immunization targeting α-synuclein and to identify the possible underlying mechanisms in a transgenic mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…↓ α-syn oligomers ↓ GCIs ↓ Demyelination ↑ Neuroprotection ↑ Motor function [145]. Passive immunization α-syn aggregation In PLP-hα-syn mice: ↓ α-syn oligomers ↓ GCIs ↑ Phagocytic microglia [148]. α-syn degradation enhancers Lithium α-syn clearance In toxin-induced models of PD: A phase II was performed but had to be terminated due to severe adverse effects [160].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…↓ α-syn oligomers ↓ GCIs ↓ Demyelination ↑ Neuroprotection ↑ Motor function [145]. Passive immunization α-syn aggregation In PLP-hα-syn mice: ↓ α-syn oligomers ↓ GCIs ↑ Phagocytic microglia [148]. α-syn degradation enhancers Lithium α-syn clearance In toxin-induced models of PD: A phase II was performed but had to be terminated due to severe adverse effects [160].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, despite transgenic animal models have contributed to identify important aspects of the disease, they artificially overexpress α-syn in oligodendrocytes, thus concealing the mechanism which triggers MSA and the accumulation of α-syn [83,204,205]. Novel strategies targeting α-syn aggregation, such as α-syn immunotherapy and small molecules, hold, however, promising therapeutic potential that still have to be evaluated in human trials [123][124][125]145,148]. In order to do that, it will be necessary to improve the design of clinical studies by selecting patient cohorts as homogeneous as possible and at early stages of the disease, before the neurodegenerative process is too advanced and neuronal rescue is still feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization with a monoclonal antibody that targeted oligomeric/prefibrillary forms of α-Syn (mAb47) mitigates the accumulation of oligomeric αSyn in the brain stem and improved motor behavioral performance (134). Recently, Kallab et al showed three antibodies (Syn-F1, Syn-O1, and Syn-O4) that specifically target oligomeric α-Syn and damped motor behavior deficit and neuroinflammation (135).…”
Section: Passive Immunization Against α-Synmentioning
confidence: 99%
“…Although therapeutic targets against α-Syn are beneficial in cellular and rodent models of PD (130,135), their translational efficacy in human clinical trials still poses a major challenge as underlying mechanisms are not fully understood.…”
Section: Future Perspectivesmentioning
confidence: 99%